Plan de comunicación corporativa para el gobierno autónomo descentralizado municipal del cantón la maná, año 2015”. - García Ayala, Gabriela Carolina (2015)
Decentralized Autonomous Government of Canton La Maná is an administrative public nonprofit entity that plans, manages and monitors the welfare of the citizenry communication planning contributed to the strengthening of its institutional. In the development of qualitative and quantitative research methodologies .The first group comprises techniques such as field observation, data collection and interview were carried Mr. Juan Villamar Cevallos Mayor municipal GAD and the head of Public Relations were implemented, the second group includes the methodology using the census to the 263 administrative employees and workers, 360 surveys were conducted to citizens of divided urban and rural parishes. The results shows that the municipal GAD plan lacks a corporate communication, internal customers are unaware of the communication structure, mission, vision, policies preventing improve institutional development. It was determined that there flaws in the external communication because the public is unaware of the activities of the institution. Communication strategies based on the goals was established, keep informed the internal customers of the activities of the local GAD, through informational signs, posters where the mission, vision, policies of the institution for external customers were specified posesionó the corporate image through billboards, social media, website in order that the public identifies the logo of the institution